Role of Public Protection Unit (SATLINMAS) Handling Covid-19 Pandemic in Surakarta City - Joko Pramono; Dora Kusumastuti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
In function of carrying out the mandate of Law Number 23 of 2014 concerning Local Government, each region recruits its citizens voluntarily to become members of Public Protection Unit (Satlinmas). One of Satlinmas duties is to carry out the disaster function. Covid-19 pandemic is also classified as a very impactful national disaster. The purpose of this study was to determine the role of Satlinmas in handling Covid-19 pandemic in Surakarta City. The method used is qualitative where data is obtained from interviews, questionnaires and involved observations. Results were analyzed using interactive analysis techniques. The conclusion is that Satlinmas primarily involved in handling Covid-19 in Surakarta City by carrying out the task of assisting related agencies in Surakarta City and stakeholders who carry out the handling of Covid-19 pandemic in Surakarta. These tasks include pre-disaster, covid-19 emergency response and post covid-19. Keywords: Disaster, Covid-19, Satlinmas